2019
DOI: 10.1002/jpln.201800560
|View full text |Cite
|
Sign up to set email alerts
|

Architectural and anatomical responses of maize roots to agronomic practices in a semi‐arid environment

Abstract: Root architecture and anatomy are important determinants of nitrogen (N) and water acquisition, but they are also environmentally plastic to adapt to N and water availability. Therefore, understanding the relationship between root traits and environmental factors is essential for improving N and water acquisition. A field experiment was conducted in the semi‐arid region of the Loess Plateau in northwestern China to quantify the architectural and anatomical root traits of maize (Zea mays L.) in response to plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…7 ). Consistent with these findings, larger xylem vessel and root diameters have been shown to develop in wheat plants in response to increased SWC caused by mulching (Zhan et al, 2019), increasing WUE and shoot biomass (Kadam et al, 2015). Although small-diameter roots maintain plant growth during a drought, especially at soil depths with available water (Comas et al, 2013), several researchers have suggested that large-diameter roots are more instrumental in resource uptake and plant growth under water scarcity (Larson and Funk, 2016, Kadam et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…7 ). Consistent with these findings, larger xylem vessel and root diameters have been shown to develop in wheat plants in response to increased SWC caused by mulching (Zhan et al, 2019), increasing WUE and shoot biomass (Kadam et al, 2015). Although small-diameter roots maintain plant growth during a drought, especially at soil depths with available water (Comas et al, 2013), several researchers have suggested that large-diameter roots are more instrumental in resource uptake and plant growth under water scarcity (Larson and Funk, 2016, Kadam et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
“…Mulching, i.e., applying a vapor diffusion barrier on the topsoil to curtail water evaporation, has been proven to enhance soil moisture content and provide enhanced transpiration (Moitra, 1996, Zhang et al, 2018, Farzi et al, 2017), plant biomass, and yields (Ramalan, 2000, Zhang, 2017a, Mukherjee, 2010). Mulching has been demonstrated to enhance leaf chlorophyll content (Wang et al, 2015), photosynthesis (Niu et al, 2020, Zhang et al, 2019), and TE (Balwinder-Singh et al, 2011), as well as improve plant root growth and roots’ architectural and anatomical properties, such as root diameter and late xylem vessel diameter, which improves water and nutrient uptake from the soil (Zhan et al, 2019, Larsson and Jensen, 1996). Low-density polyethylene sheets approximately 0.1 mm thick have been used extensively for mulching in developed countries (Kasirajan and Ngouajio, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While intrinsically a small and superficial part of the overall RSA, the crown is the information-dense nexus. Root crown analysis has been effective across a diversity of research topics ranging from the effect of agricultural practices on root growth [20], drought-induced root traits [21], the identification of QTLs [22], and mutant analysis [23]. However, the desire for non-destructive measurements across the entire root system prompted the development of rhizotrons, large subterranean chambers where roots in physical contact with clear walls can be studied, requiring extensive long-term infrastructure [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…To link brace root phenotypes to root lodging resistance and anchorage necessitates a high throughput brace root phenotyping workflow. Current root phenotyping methods are either labor intensive, rely on subjective manual data collection, and/or are not targeted for brace root phenotyping (Trachsel et al, 2011; Das et al, 2015; Zhan et al, 2019; Salungyu et al, 2020, Sanguineti et al, 1998; Liu et al, 2012; Sharma and Carena, 2016). Thus, we developed a workflow that non-destructively captures RGB (Red Green Blue) images using a ground-based robot and extracts brace root phenotypes through a semi-automated root tagging pipeline.…”
Section: Introductionmentioning
confidence: 99%